UPAYA MENINGKATKAN MUTU PAI MELALUI KEGIATAN EKSTRAKURIKULER KEAGAMAAN DI SD ISLAM SE-KOTA SALATIGA - Nashrul Haqqi Firmansyah (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
This study examines the religious extracurricular program as a means of improving the quality of Islamic Religious Education and achieving the objectives of Islamic education. Religious extracurricular activities have a positive effect on student academic achievement and can support the teaching and learning process. The existence of religious extracurricular is deemed necessary to support the achievement of the objectives of Islamic Religious Education learning. The general objective of this research is to describe religious extracurricular activities, find efforts to improve the quality of Islamic Religious Education through religious extracurricular activities and find out the factors that influence efforts to improve the quality of Islamic Religious Education through religious extracurricular activities in Islamic elementary schools in Salatiga. The researcher chose Islamic elementary school in Salatiga city because besides having a religious extracurricular program, Islamic elementary school in Salatiga city is also a school that implements Islamic values in its school environment. To get the results of the study, a descriptive method was used with a qualitative approach and observation techniques, interviews and documentation. The data of this study were sourced from the Principal, Student Waka, PAI Teachers, and Extracurricular Trainers in Islamic elementary schools in Salatiga. From this research, it was found that the implementation of Islamic Religious Education learning which was carried out, in general, went smoothly and conducive, and had already used varied learning methods. As for the implementation of religious extracurricular programs in Islamic elementary schools in Salatiga city, they differ from one school to another, with different management and strategies. In addition, each extracurricular trainer directs students to know the five aspects of the PAI curriculum not only in cognitive abilities but also in the affective and psychomotor domains. To achieve this goal, Islamic elementary schools in the city of Salatiga optimize the supporting factors and try to anticipate the existing inhibiting factors.